2009
DOI: 10.1111/j.1349-7006.2008.01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Formosanin C‐induced apoptosis requires activation of caspase‐2 and change of mitochondrial membrane potential

Abstract: (1) The plant has been used as a folk remedy for snake-bite inflammation and tumors. The crude extract of Paris formosana Hayata (Liliaceae) has also been revealed to inhibit the growth of various cultured cancer cell lines.(2) Formosanin C, a diosgenin saponin, a major constituent in the methanol extract of Paris formosana Hayata (Liliaceae), has already been shown to exert a cytotoxic effect on the mouse hepatocellular MH134 cell line injected subcutaneously in C3H/HeN mice, especially in combination with 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 25 publications
(42 reference statements)
2
35
0
Order By: Relevance
“…While future studies will further determine the nature of PSII-induced apoptosis in ovarian cancer tumor cells, data from the present studies suggest that PSII treatment affects the mitochondrial apoptotic pathways. Indeed, these findings are supported by a study by Lee et al showing PSII-formosanin C induces mitochondria membrane potential collapse and the activation of essential components of the intrinsic apoptosis pathway (17).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…While future studies will further determine the nature of PSII-induced apoptosis in ovarian cancer tumor cells, data from the present studies suggest that PSII treatment affects the mitochondrial apoptotic pathways. Indeed, these findings are supported by a study by Lee et al showing PSII-formosanin C induces mitochondria membrane potential collapse and the activation of essential components of the intrinsic apoptosis pathway (17).…”
Section: Discussionsupporting
confidence: 53%
“…However, the field investigating the antitumor properties of Paris saponin has only become more active in the past five years. Multiple model systems ranging from murine lung adenocarcinoma (22), human colon adenocarcinoma grade II (17), mouse lung adenocarcinoma (23) to zebrafish embryos have demonstrated that several Paris saponins can induce programmed cell death, inhibit cell migration, and inhibit tumor cell growth. Studies from our laboratories have also unraveled PSI mechanisms of action on ovarian cancer cells (5,24,33,36,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caspase activation leads to proteolytic cleavage of specific cell substrates, including PARP (27), lamins, histone H1, as well as proteins involved in cell growth, survival and death (28). Many natural components of plant extracts induce apoptosis in HT-29 cells with caspase-3 activation and PARP cleavage (29,30). However, diosgenin-induced apoptosis in HT-29 cells was PARP-independent in comparison with HCT-116 cells where PARP cleavage was present as previously described (10).…”
Section: Discussionmentioning
confidence: 62%
“…3 All these effects depended on the sugar moiety in the structure of formosanin C. Meanwhile, FC induced apoptosis of HT-29 cells through activation of caspase-2 and the dysfunction of mitochondria. 4 Our preliminary drug screening revealed that RPS extracted from Paris polyphylla had strong anti-lung cancer activity. [5][6][7] Formosanin C acting as the main effective constituent in RPS should be studied in detail including its antitumor and antimetastatic effects.…”
Section: Introductionmentioning
confidence: 95%